2002
DOI: 10.4269/ajtmh.2002.67.459
|View full text |Cite
|
Sign up to set email alerts
|

The population structure of Plasmodium falciparum and Plasmodium vivax during an epidemic of malaria in the Eastern Highlands of Papua New Guinea.

Abstract: Abstract. Although most of the Papua New Guinea highlands are too high for stable malaria transmission, local epidemics are a regular feature of the region. Few detailed descriptions of such epidemics are available, however. We describe the investigation of a malaria epidemic in the Obura Valley, Eastern Highlands Province, Papua New Guinea. Of the 244 samples examined by microscopy, 6.6% were positive for Plasmodium falciparum only, 9.4% were positive for Plasmodium vivax only, and 1.2% were mixed infections.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
45
0

Year Published

2003
2003
2019
2019

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 52 publications
(47 citation statements)
references
References 22 publications
2
45
0
Order By: Relevance
“…The simplicity of this picture is remarkable; the mutations that contribute to pyrimethamine resistance appear to be the same worldwide, synonymous substitutions are very rarely observed, and only one insertion has ever been reported (7). These patterns support the idea that the present P. falciparum populations have evolved recently from a few founders and spread virtually worldwide from these foci, probably influenced by the strong selection pressure of drug treatment (6,42,51,67).Limited studies to date have demonstrated that there is a far higher level of overall genetic diversity in the P. vivax population than one observes in the P. falciparum population (9,16,29,41). This difference is likely to be important to the evolution of drug resistance.…”
supporting
confidence: 73%
“…The simplicity of this picture is remarkable; the mutations that contribute to pyrimethamine resistance appear to be the same worldwide, synonymous substitutions are very rarely observed, and only one insertion has ever been reported (7). These patterns support the idea that the present P. falciparum populations have evolved recently from a few founders and spread virtually worldwide from these foci, probably influenced by the strong selection pressure of drug treatment (6,42,51,67).Limited studies to date have demonstrated that there is a far higher level of overall genetic diversity in the P. vivax population than one observes in the P. falciparum population (9,16,29,41). This difference is likely to be important to the evolution of drug resistance.…”
supporting
confidence: 73%
“…These data suggest that this mutation has arisen recently, and although it has had time to spread among the Papua New Guinea and Western Papua populations to relatively high frequencies, apparently there has not been time for recombination or point mutations at other positions to generate new alleles bearing this mutation. A parallel situation occurs with the T 590 mutation, which has also been detected in the Papua New Guinea Highlands (34).…”
Section: Discussionmentioning
confidence: 66%
“…A focal outbreak of P. falciparum malaria caused by a clonal parasite line was documented on Santiago Island, Cape Verde (32), and among Amazonian Yanomami Amerindians (45). A previous study conducted during a malaria epidemic in the eastern highlands of Papua New Guinea showed that all P. falciparum infections shared a single genotype, suggesting external introduction as the epidemic source, while the P. vivax infections were highly diverse, suggesting endemic transmission (46). To our knowledge, the 2002 Aneityum outbreak is the first documented outbreak of P. vivax malaria caused by a semiclonal parasite line.…”
Section: Discussionmentioning
confidence: 99%